2004
DOI: 10.1300/j069v23n01_07
|View full text |Cite
|
Sign up to set email alerts
|

An Open-Label Pilot Study of Methylphenidate in the Treatment of Cocaine Dependent Patients with Adult Attention Deficit/ Hyperactivity Disorder

Abstract: A multi-site, open-label study of methylphenidate for treating patients with comorbid diagnoses of attention deficit/hyperactivity disorder and cocaine dependence was performed. Forty-one participants, who met DSM-IV criteria for adult attention deficit/hyperactivity disorder and cocaine dependence, were enrolled into this ten week outpatient study. The targeted total daily dose of methylphenidate was 60 mg (20 mg TID). Participants received individual substance abuse therapy throughout the trial. Safety measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 22 publications
0
17
1
1
Order By: Relevance
“…A singular RCT of immediate-and sustained-release methamphetamine indicated that the latter formulation reduced cocaine craving and use (Mooney et al, 2009). Mixed evidence for the therapeutic effects of methylphenidate among cocaine-dependent patients -especially those also suffering from ADHD disorders -have been observed; these may be more favourably associated with sustained over immediate release formulations (Arria & Wish, 2006;Levin, Evans, Brooks, & Garawi, 2007;Prudhomme-White, Becker-Blease, & Grace-Bishop, 2006;Schubiner et al, 2002;Somoza et al, 2004).…”
Section: Pharmaco-therapeutic Interventionsmentioning
confidence: 99%
“…A singular RCT of immediate-and sustained-release methamphetamine indicated that the latter formulation reduced cocaine craving and use (Mooney et al, 2009). Mixed evidence for the therapeutic effects of methylphenidate among cocaine-dependent patients -especially those also suffering from ADHD disorders -have been observed; these may be more favourably associated with sustained over immediate release formulations (Arria & Wish, 2006;Levin, Evans, Brooks, & Garawi, 2007;Prudhomme-White, Becker-Blease, & Grace-Bishop, 2006;Schubiner et al, 2002;Somoza et al, 2004).…”
Section: Pharmaco-therapeutic Interventionsmentioning
confidence: 99%
“…Two laboratory studies in humans have reported decreased subjective and reinforcing effects of cocaine in individuals maintained on oral MPD (Collins et al, 2006;Winhusen et al, 2006). Results of clinical trials, however, have been mixed in terms of the ability of MPD to decrease cocaine-positive urines (Grabowski et al, 1997;Schubiner et al, 2002;Somoza et al, 2004;Levin et al, 2007). Possible confounding variables in these studies include the presence of ADHD and relatively small sample sizes.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that ADHD symptoms may negatively affect the outcome of substance abuse treatment and that, conversely, treatment of ADHD with stimulants may facilitate substance abuse treatment (Schubiner, 2005;Wilens, 2004). Despite concerns that stimulant medications may be contraindicated for use by substance abusers due to the risk of relapse (Levin et al, 1999), preliminary evidence suggests that the use of MPH may be safe and effective for treating ADHD in cocaine dependent adults when it is used as prescribed, that it does not worsen symptoms of, and may even lead to improvement in, cocaine dependence (e.g., Levin et al, 2007;Schubiner et al, 2002;Somoza et al, 2004). However, the propensity for substance abusers with ADHD to misuse their prescribed MPH itself has not been adequately explored.…”
Section: Introductionmentioning
confidence: 99%